Associação entre o estresse percebido dos pais e distúrbios do sono com o possível bruxismo do sono em crianças e adolescentes com transtorno do espectro autista: um estudo preliminar - José Gabriel Victor Costa Silva (2023)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder related to social interaction problems, communication difficulties, repetitive behavior and sensory sensitivity. Children and adolescents with ASD may have a higher occurrence of oral health problems, such as bruxism. There are few studies evaluating sleep bruxism in these individuals, although it is a significant problem in this population. Thus, this study aims to investigate the association between possible sleep bruxism (PSB) in children and adolescents with ASD with the parents/guardians’ perceived stress and with children/adolescents’ sleep disturbances. A cross-sectional study was carried out with children/adolescents with ASD, aged 5 to 19 years old, and their parents/guardians at Fundação Centro Integrado de Apoio ao Portador de Deficiência (FUNAD) in Paraíba. Parents/guardians answered a socio-demographic and child/adolescent’s characteristics questionnaire, which collected data on schooling, degree of kinship with the child, family income, number of children, age and sex of the child, functional level of autism and use of medication for ASD. PSB was diagnosed based on parents/guardians' reports on the presence or absence of teeth grinding/clenching behavior in children/adolescents during sleep. The Perceived Stress Scale (BPSS-10) was used to assess the parents/guardians’ stress. Its total score can vary from 0 to 40 points, and the higher the score, the greater the perceived stress. The Sleep Disturbance Scale for Children (SDSC) was used to investigate possible children/adolescents’ sleep disturbances, which has 26 items, with 5 answer options, with a higher score on the questionnaire representing greater clinical severity of the symptoms. The SDSC further classifies sleep disturbances into six categories: (1) disorders of initiating and maintaining sleep; (2) sleep-disordered breathing; (3) disorders of arousal; (4) sleep-wake transition disorders; (5) disorders of excessive somnolence and (6) sleep hyperhidrosis. The data obtained were statistically analyzed using Statistical Package for the Social Sciences (SPSS), version 22.0. Descriptive, bivariate, and unadjusted and adjusted Poisson Regression analyzes were performed (PR, CI=95%; p<0.05). The preliminary sample of the present study was composed by 50 children/adolescents with ASD, 84% (n=42) male. PSB in children and adolescents with ASD was reported by 28% (n=14) of parents/guardians. The mean score of parents/guardians’ perceived stress was 20.38 (±8.535) and 48.84 (±17.552) for children/adolescents’ sleep disorders. The final adjusted Poisson Regression model revealed an association between PSB and higher scores on the Perceived Stress Scale by parents/guardians (PR: 1.05; 95%CI: 1.01-1.09; p=0.013); and the categories of sleep-disordered breathing (PR: 1.14; 95%CI: 1.05-1.24; p=0.002) and sleep hyperhydrosis (PR: 1.15; 95%CI: 1.01-1 .31; p=0.039) of the SDSC. The prevalence of PSB in children and adolescents with ASD was 28% and was associated with parents/guardians’ higher levels of perceived stress, in addition to the categories of children/adolescents’ sleep-disordered breathing and sleep hyperhydrosis.